Administration Building, Dawson - Howard, Mart Albert, 1855-1926 (Manuscripts, Archives, and Special Collections, Washington State University Libraries: https://libraries.wsu.edu/masc, 1898)
1 Lantern Slide: b&w; 10 x 8 cm. Construction activities around Dawson's Territorial Administration Building, now the Dawson City Museum.